2011
DOI: 10.1002/ep.10591
|View full text |Cite
|
Sign up to set email alerts
|

Longterm forecasting of solid waste generation by the artificial neural networks

Abstract: This study presents a new approach—preprocessing for reaching the stationary chain in time series—to unravel the interpolating problem of artificial neural networks (ANN) for long‐term prediction of solid waste generation (SWG). To evaluate the accuracy of the prediction by ANN, comparison between the results of the multivariate regression model and ANN is performed. Monthly time series datasets, by the yrs 2000–2010, for the city of Mashhad, are used to simulate the generated solid waste. Different socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…These data‐driven models without need of complete perception of MSWG process have high ability to model waste generation changes over times. Artificial neural network (ANN) and Adaptive Neuro‐Fuzzy Inference System are such artificial intelligence models that have been used for prediction of MSWG . These models have a good ability of MSWG prediction but the innate disadvantage such as over‐fitting training, local minimum, difficulty in determination of network architecture, and poor generalizing performance remain unsolved and limit the application of the ANN approach into practice.…”
Section: Introductionmentioning
confidence: 99%
“…These data‐driven models without need of complete perception of MSWG process have high ability to model waste generation changes over times. Artificial neural network (ANN) and Adaptive Neuro‐Fuzzy Inference System are such artificial intelligence models that have been used for prediction of MSWG . These models have a good ability of MSWG prediction but the innate disadvantage such as over‐fitting training, local minimum, difficulty in determination of network architecture, and poor generalizing performance remain unsolved and limit the application of the ANN approach into practice.…”
Section: Introductionmentioning
confidence: 99%
“…We found that our model captured similarly slightly higher amount of variability in MSW generation. A monthly model for Mashhad city, Iran explained 70% of variability in MSW generation, while a preprocessed ANN model explained 73% [33,34]. A recent seasonal model explained 73% of MSW generation variability [24].…”
Section: Resultsmentioning
confidence: 99%
“…Since socioeconomic data have been associated with MSW generation by previous researches, GDP, unemployment rate, and income were chosen as socioeconomic indicators. The correlation between MSW and meteorological condition has also been addressed in some studies . Maximum temperature and rain were also considered as meteorological indicators.…”
Section: Adaptive Neuro‐fuzzy Inference Systemmentioning
confidence: 99%
“…The independent variables used for modelling of ANN1/1 and ANN1/2 models were year (2013-2016) and month (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), while the output variables were the socioeconomic (ANN1/1) and waste management (ANN1/2) variables for the period from 2013 to 2016. ANN1/1 model was also used to predict the socio-economic indicators in 2017, according to a model developed using the data for a period between 2013 and 2016.…”
Section: Discussionmentioning
confidence: 99%